Tocolysis among Women with Preterm Birth: Associated Factors and Outcomes from a Multicenter Study in Brazil - Tabata Zumpano Dias; Mariana Lacerda Fava; Renato Passini Júnior; Jose Guilherme Cecatti; Ricardo Porto Tedesco; Giuliane Jesus Lajos; Patricia Moretti Rehder; Marcelo Luis Nomura; Paulo Fanti Oliveira; Maria Laura Costa (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2018)
Abstract Objective To evaluate the use of tocolysis in cases of preterm birth due to spontaneous preterm labor in a Brazilian sample. Methods A sample of 1,491 women with preterm birth due to spontaneous preterm labor were assessed, considering treatment with tocolysis or expectant management, according to gestational age at birth (< 34 weeks and 34 to 36 þ 6 weeks) and drugs prescribed. The study took place in 20 Brazilian hospitals from April 2011 to July 2012. Bivariate analyses were conducted to evaluate associations with sociodemographic and obstetric characteristics and odds ratios with their respective 95% confidence intervals were estimated for maternal and neonatal outcomes. Results A total of 1,491 cases of preterm birth were considered. Tocolysis was performed in 342 cases (23%), 233 of which (68.1%) were delivered before 34 weeks. Within the expectant management group, 73% was late preterm and with more advanced labor at the time of admission. The most used drugs were calcium channel blockers (62.3%), followed by betamimetics (33%). Among the subjects in the tocolysis group, there were more neonatal and maternal complications (majority non-severe) and an occurrence of corticosteroid use that was 29 higher than in the expectant management group. Conclusion Tocolysis is favored in cases of earlier labor and also among thosewith less than 34 weeks of gestation, using preferably calcium channel blockers, with success in achieving increased corticosteroid use. Tocolysis, in general, was related to higher maternal and neonatal complication rates, which may be due to the baseline difference between cases at admission. However, these results should raise awareness to tocolysis use.